Au nanowire modified with tannic acid for enhanced electrochemical synthesis of ammonia. (September 2021) - Liu, Songliang; Yin, Shuli; Jiao, Shiqian; Zhang, Hugang; Wang, Ziqiang; Xu, You; Li, Xiaonian; Wang, Liang; Wang, Hongjing
Abstract: Electrochemical N2 reduction reaction (NRR) under ambient conditions provides sustainable and green pathways; meanwhile, efficient electrocatalysts are strongly required. In this work, we report an interfacial active site strategy to improve the electrocatalytic NRR performance by modification of Au nanowire (Au NW) surface with oxygen-rich tannic acid (TA). Benefiting from their ultrafine one-dimensional nanowire architecture and the TA-modified metallic interface, the TA-Au NWs effectively facilitate the adsorption and activation of reactants. The TA-Au NWs exhibit a large NH3 yield rate (15.71 μg h −1  mg −1 cat. ) and a high Faraday efficiency of 14.83% at −0.3 V (vs. the reversible hydrogen electrode) in a N2 -saturated 0.1 M Na2 SO4 with an excellent electrochemical durability. This work provides a general surface modification strategy to fabricate highly active NRR electrocatalysts. Graphical abstract: Image 1 Highlights: Tannic acid–modified Au nanowires were prepared via a two-step approach. The catalysts combined the interfacial sites with one-dimensional structure. The catalysts exhibit excellent performance for N2 reduction reaction (NRR). The surface modification strategy could enhance various applications, beyond NRR.